Technology-supported home monitoring in heart failure patients. (25th November 2020) - Rahimi, K; Nazarzadeh, M; Pinho-Gomes, A.C; Woodward, M; Salimi-Khorshidi, G.H; Ohkuma, T; Fitzpatrick, R; Tarassenko, L; Denis, M; Cleland, J
Abstract: Background: Digital health promises to enhance the prevailing episodic models of chronic heart failure (HF) care. Purpose: We aimed to test the hypothesis that digital home monitoring with centralised specialist support for remote management of HF and major vascular comorbidities is more effective in optimising medical therapy and improving patients' quality of life than digital home monitoring alone. Methods and results: In a two-armed partially blinded parallel randomised controlled trial, seven sites in the United Kingdom recruited a total of 202 adults with HF (71.3 years SD 11.1; mean left ventricular ejection fraction 32.9% SD 15.4). Participants were selected for being at high risk of adverse outcomes or high potential to benefit from remote management. Participants in both study arms were given an internet-enabled tablet computer, Bluetooth-enabled blood pressure monitor and weighing scales for health monitoring. After a run-in period, participants randomized to intervention received additional regular feedback to support self-management and their primary care doctors received instructions on blood investigations and pharmacological treatment. The primary outcome was the use of recommended medical therapy, for chronic HF and major comorbidities, measured as a composite opportunity score. Co-primary outcome was change in physical score of Minnesota Living with Heart failure questionnaire. At the end of the trial, the weighted opportunity score was 0.54 (CI 95% 0.46, 0.62) in the control group and 0.61 (CI 95% 0.52, 0.70) in the intervention arm (p for mean difference=0.25). Physical well-being of participants did not differ significantly between the groups either (p=0.55). Conclusions: Central provision of tailored specialist management in a multimorbid HF population was feasible. However, there was no strong evidence for improvement in use of evidence-based therapies nor health-related quality of life. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): National Institute for Health Research (NIHR) Health Services Research and Delivery; NIHR Career Development Fellowship